2015
DOI: 10.1007/s11207-015-0782-0
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the 30 THz Emission Detected During the Solar Flare on 2012 March 13 at 17:20 UT

Abstract: Solar observations in the infrared domain can bring important clues on the response of the low solar atmosphere to primary energy released during flares. At present the infrared continuum has been detected at 30 THz (10 µm) in only a few flares. SOL2012-03-13 , which is one of these flares, has been presented and discussed in Kaufmann et al. (2013). No firm conclusions were drawn on the origin of the mid-infrared radiation. In this work we present a detailed multi-frequency analysis of the SOL2012-03-13 event,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 37 publications
6
34
0
1
Order By: Relevance
“…In our case, if the emission were optically thick gyrosynchrotron, the spectral index between 212 and 405 GHz, α ≃ 0.8, would indicate an inhomogeneous source (Klein & Trottet, ; Simões & Costa, ), while Tsap et al () propose a mixture of gyrosynchrotron and thermal bremsstrahlung absorption to explain the spectral increase between 93 and 140 GHz during SOL2012‐07‐05T11:44. The mid‐IR flux can be explained, as in Trottet et al (), as optically thin thermal bremsstrahlung emission of a heated chromospheric plasma, since fluxes of the two events are similar. Moreover, Simões et al (), using radiative hydrodynamic simulations, have demonstrated that the mid‐IR emission from solar flares may be accounted by optically thin thermal bremsstrahlung due to the increase of the electron density in the chromosphere, as a consequence of the ionization of hydrogen under non local thermodynamical equilibrium (non‐LTE) conditions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our case, if the emission were optically thick gyrosynchrotron, the spectral index between 212 and 405 GHz, α ≃ 0.8, would indicate an inhomogeneous source (Klein & Trottet, ; Simões & Costa, ), while Tsap et al () propose a mixture of gyrosynchrotron and thermal bremsstrahlung absorption to explain the spectral increase between 93 and 140 GHz during SOL2012‐07‐05T11:44. The mid‐IR flux can be explained, as in Trottet et al (), as optically thin thermal bremsstrahlung emission of a heated chromospheric plasma, since fluxes of the two events are similar. Moreover, Simões et al (), using radiative hydrodynamic simulations, have demonstrated that the mid‐IR emission from solar flares may be accounted by optically thin thermal bremsstrahlung due to the increase of the electron density in the chromosphere, as a consequence of the ionization of hydrogen under non local thermodynamical equilibrium (non‐LTE) conditions.…”
Section: Discussionmentioning
confidence: 94%
“…The first observation at 10 μm (30 THz) was reported by Kaufmann et al () for the Geostationary Operational Environmental Satellite (GOES) M2 event SOL2012‐03‐13T17:20, which also exhibited white light (WL) emission with a remarkable coincidence both in space and in time. Trottet et al () interpret the mid‐IR emission as optically thin thermal from the chromosphere heated by precipitating electrons and ions. Penn et al () observed the C7 event SOL2014‐09‐24T17:50 with two cameras with filters centered at 5.2 and 8.2 μm (57.7 and 36.6 THz, respectively) and high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these models are currently widely used (e.g., Heinzel & Avrett 2012;Trottet et al 2015;Kleint et al 2016;Simões et al 2017). When velocity or the position of the flare transition region is modified in phenomenological models, the gas density must also change and is not correctly given by hydrostatic equilibrium.…”
Section: Discussion and Applicationmentioning
confidence: 99%
“…For a complete description of the observational data see Kaufmann et al (2013) and Trottet et al (2015); both works focus on the analysis of the 30 THz emission. In particular Trottet et al (2015) concluded that its origin is compatible with thermal radiation that originate from two different sources: 80% of the emission comes from a T ∼ 8000 K optically thin source at chromospheric heights, while the remaining 20% is emitted by an optically thick photospheric source with T ∼ 6000 K. Furthermore, Trottet et al (2015) interpret the chromospheric temperature excess that produces the 30 THz emission with the energy deposited by non-thermal electrons. The same accelerated electron distribution is responsible for the thick-target bremsstrahlung hard X-ray and the GS submillimeter radiation.…”
Section: Overview Of the Flarementioning
confidence: 99%
“…The same accelerated electron distribution is responsible for the thick-target bremsstrahlung hard X-ray and the GS submillimeter radiation. For the HXR emission Trottet et al (2015) found an electron distribution with two spectral indices, and a break energy at around 400 keV. On the other hand, the GS optically thin emission is compatible with a source of electrons with energies 800 ≤ E e ≤ 10 4 keV, having a trapping time of around 2 s, gyrating in a magnetic field with effective intensity B • ∼ 700 G. All these GS parameters were deduced for an homogeneous emitting source with a presupposed size.…”
Section: Overview Of the Flarementioning
confidence: 99%